The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/0100-5405/2103
|View full text |Cite
|
Sign up to set email alerts
|

Bioatividade de indutores de resistência no manejo da antracnose da goiabeira (Psidium guajava L.)

Abstract: RESUMO A cultura da goiaba apresenta perdas em torno de 40 a 60% na pós-colheita relacionadas a problemas fitossanitários, como a antracnose causada pelo fungo Colletotrichum gloeosporioides. Pesquisas com métodos alternativos utilizando indutores de resistência têm sido bastante promissoras na busca de produtos com alto potencial no controle de patógenos em pós-colheita. Assim, o presente trabalho teve como objetivo avaliar os indutores de resistência no controle da antracnose e seus efeitos na qualidade físi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The organic acids (ascorbic, citric, and lactic) and the bioflavonoids give an antioxidant action to Ecolife  ; together with the peptides, they act as microbiostatic agents, assisting the balance of the microbial flora (Motoyama et al, 2003). Several authors describe, in their researches, the fungistatic capacity of Ecolife  in vitro (Cruz et al, 2011;Gomes et al, 2016). Other authors observed that, for Ecolife  , the antimicrobial activity was dose-dependent (Motoyama et al, 2003;Barguil et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The organic acids (ascorbic, citric, and lactic) and the bioflavonoids give an antioxidant action to Ecolife  ; together with the peptides, they act as microbiostatic agents, assisting the balance of the microbial flora (Motoyama et al, 2003). Several authors describe, in their researches, the fungistatic capacity of Ecolife  in vitro (Cruz et al, 2011;Gomes et al, 2016). Other authors observed that, for Ecolife  , the antimicrobial activity was dose-dependent (Motoyama et al, 2003;Barguil et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, application of elicitors did not result in the activation of any mechanism associated with increased betalain production in beetroot. Previous studies on the use of elicitors to control pathogens demonstrated that compounds were able to suppress and/or damage nematodes, as evidenced by the decrease in infection area size, disease severity, or pathogen proliferation (Gomes et al, 2016;Neumann Silva et al, 2017;Antonio et al, 2018). Here such effects resulted in a decrease in RF.…”
Section: Lignification Of Plant Cells Increases Wall Rigidity Conferringmentioning
confidence: 99%
“…Apesar dos indutores fosfito de potássio e biomassa cítrica apresentarem pouca ação fungitóxica sobre C. cassiicola, verificou-se que o indutor biomassa cítrica obteve CE50 inibitória da germinação de esporos menor que 10 µg mL -1 . O indutor biomassa cítrica, quando aplicado em bananas, mostrou-se eficiente na erradicação dos conídios de Mycosphaerella fijiensis aderidos à casca dos frutos, inibindo totalmente a germinação dos conídios(Hanada et al, 2004) Gomes et al (2016). constataram efeito inibitório de biomassa cítrica no crescimento de Colletotrichum gloeosporioides in vitro.…”
unclassified